Synthesis and Structure of Hexakis(Imidazole) Cobalt(II) Dichloride Monohydrate - Zhang, Shu-Sheng; Niu, Shu-Yan; Shi, Xin; Li, Xue-Mei; Wen, Yong-Hong; Jiao, Kui (Asian Journal of Chemistry, 2010)
The crystal and molecular structures of [Co(Im)6]Cl2.2H2O (Im = imidazole) have been determined by X-ray crystallography. It crystallizes in the triclinic system, space group P-l, with cell dimensions of a = 8.792(2), b = 9.067(2), c = 10.562(2) Å, α = 75.13(3)º, β = 83.12(3)º, γ = 61.78(3)º and Z = 1. The crystal structure of the title compound is composed of three parts, viz., the hexakis(imidazole)cobalt(II) cation, the chlorine anions and aqua molecule. The cobalt(II) ions have an octahedral geometry with the CoN6 chromophore. The water molecule plays important roles in the structure acting as a bridge between the cation and anion moieties. The whole molecules are linked into two-dimensional framework perpendicular to the b-axis.